Colloidal synthesis of Cu2−xAgxCdSnSe4 nanocrystals: microstructures facilitate high performance thermoelectricity. Issue 47 (17th November 2015) - Chen, Qiufan; Wang, Guiwen; Zhang, Aijuan; Yang, Dingfeng; Yao, Wei; Peng, Kunling; Yan, Yanci; Sun, Xiaonan; Liu, Anping; Wang, Guoyu; Zhou, Xiaoyuan
Abstract : We have demonstrated Cu2− x Ag x CdSnSe4 nanocrystals can result in decreases in the lattice thermal conductivity while increasing the Seebeck coefficient. A ZT up to 0.8 was obtained when x is 0.3. Abstract : In this study, we report the colloidal synthesis (CS) of quaternary chalcogenide Cu2− x Ag x CdSnSe4 nanocrystals ( x = 0, 0.1, 0.2, 0.3, and 0.4) and their application in thermoelectrics. The as-prepared Cu2− x Ag x CdSnSe4 nanocrystals present a narrow size distribution ranging from 30 to 50 nm and a precisely controlled composition. Additionally, it was observed that the disordered zinc blende phases were embedded in the normal zinc blende phases and amorphous nanoparticles were dispersed on grain surfaces and between grain boundaries of spark plasma sintered bulk Cu2− x Ag x CdSnSe4 . Moreover, a large enhancement in the Seebeck coefficient and a dramatically reduced lattice thermal conductivity was found in Cu2− x Ag x CdSnSe4 solid solution, resulting in the dimensionless thermoelectric figure of merit reaching a peak value of 0.8 at 688 K when x = 0.3. This represents a 44% and 83% improvement in comparison to the undoped sample and the sample made via the solid state method (SS), respectively. The results demonstrate an exciting scientific opportunity to raise the figure-of-merit of quaternary chalcogenide Cu2 CdSnSe4 prepared by colloidal synthesis via optimized solid solution.